2002
DOI: 10.1159/000067540
|View full text |Cite
|
Sign up to set email alerts
|

OCT Findings in Patients with Retinopathy after Watching a Solar Eclipse

Abstract: Purpose: To evaluate the optical coherence tomography (OCT) findings in patients with solar retinopathy after watching a solar eclipse. Methods: Complete ocular examinations and OCT were done in 4 patients presenting with acute solar retinopathy soon after observation of an eclipse. All 4 patients repeated the examinations about 1 month and 1 year after the first visit. Results: The symptoms and fundus findings were similar in all patients; all eyes were emmetropic. However, the OCT images were different in al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0
9

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(34 citation statements)
references
References 4 publications
2
23
0
9
Order By: Relevance
“…Está relacionada con la intensidad, tiempo de exposición y longitud de onda de la fuente lumínica, siendo la luz azul y ultravioleta (longitud de onda menor a 300-350 nm) la más dañina para el ojo (3)(4)(5). Clínicamente se caracteriza por una lesión amarillenta a nivel foveal, un defecto ventana en la AGF y un escotoma central o paracentral que con el tiempo disminuye.…”
Section: Discussionunclassified
“…Está relacionada con la intensidad, tiempo de exposición y longitud de onda de la fuente lumínica, siendo la luz azul y ultravioleta (longitud de onda menor a 300-350 nm) la más dañina para el ojo (3)(4)(5). Clínicamente se caracteriza por una lesión amarillenta a nivel foveal, un defecto ventana en la AGF y un escotoma central o paracentral que con el tiempo disminuye.…”
Section: Discussionunclassified
“…Las radiaciones solares producen un daño puntual en los melanosomas apicales del EPR seguido de alteraciones en el segmento más externo de los fotorreceptores foveolares (1,5). El defecto depende directamente de la intensidad, la duración, el espectro de exposición, la dilatación pupilar, la transparencia de medios, la capacidad de enfoque y la refracción, con un riesgo mayor los emétropes o hipermétropes leves, en los que las radiaciones se transmiten directamente a la fóvea (4).…”
Section: Discussionunclassified
“…Las alteraciones descritas por OCT-III demuestran principalmente áreas de excavación en las capas hiperreflectantes del EPR y de los segmentos más externos de la capa de fotorreceptores (1,2,4). Algunos autores han descrito por OCT la presencia de un punto hiperreflectante en la cavidad vítrea a unas 70 µm de la retina (4).…”
Section: Discussionunclassified
“…However there is often little or no abnormality in solar retinopathy, although in severe cases there may be a window defect caused by retinal pigment epithelium (RPE) atrophy. 2 OCT findings in acute solar retinopathy were first described by Codenotti et al 4 OCT studies in chronic solar retinopathy describe hyporeflective spaces at the level of the outer photoreceptor segments and RPE. These may involve the entire photoreceptor layer in more severe cases, together with overlying neurosensory thinning.…”
Section: Commentmentioning
confidence: 95%
“…3 Positive stain with CD68 (a macrophage marker) can be explained by the intracytoplasmic accumulation of phagolysosomes and does not reflect a histiocytic origin. 4 Additionally, it has been shown that the granular cells are also positive for inhibin-a. 3 Although inhibin-a has been demonstrated to be strongly supportive of a granular cell tumour, the relation between this expression and pathogenesis of the granular cell tumour is unclear.…”
Section: Commentmentioning
confidence: 99%